Implementasi Konsep Asthabrata sebagai Landasan Hidup Generasi Z - Haryo Untoro; Daffa Pharaja Mustofa; Miktahul Ulumudin (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
Generation Z is often referred to as the